Dysfibrinogenemia—Potential Impact of Genotype on Thrombosis or Bleeding - Bor, Mustafa Vakur; Feddersen, Søren; Pedersen, Inge Søkilde; Sidelmann, Johannes Jakobsen; Kristensen, Søren Risom (Seminars in Thrombosis and Hemostasis, 2021)
The congenital dysfibrinogenemias, most often associated with bleeding disorders, encompass mutations in the amino-terminal end of fibrinogen α-chain consisting of Gly17-Pro18-Arg19-Val20, known as knob A, which is a critical site for fibrin polymerization. Here we review the studies reporting dysfibrinogenemia due to mutations affecting fibrinogen knob A and identified 29 papers. The number of reports on dysfibrinogenemias related to residues Gly17, Pro18, Arg19, and Val20 is 5, 4, 18, and 2, respectively. Dysfibrinogenemias related to residues Gly17, Pro18, and Val20 are exclusively associated with bleeding tendency. However, the clinical picture associated with dysfibrinogenemia related to residue Arg19 varies, with most patients suffering from bleeding tendencies, but also transitory ischemic attacks and retinal thrombosis may occur. The reason for this variation is unclear. To elaborate the genotype–phenotype associations further, we studied a Danish family with knob A-related dysfibrinogenemia caused by the Aα Arg19Gly (p.Arg19Gly) mutation using whole-exome sequencing and fibrin structure analysis. Our family is the first reported carrying the p.Arg19Gly mutation combined with one or more single nucleotide polymorphisms (SNP)s in FGA, FGB, and/or FGG and increased fibrin fiber thickness and fibrin mass-to-length ratio suffering from pulmonary emboli, suggesting that compound genotypes may contribute to the thrombogenic phenotype of these patients. Our review, accordingly, focuses on significance of SNPs, compound genotypes, and fibrin structure measures affecting the genotype–phenotype associations in fibrinogen knob A mutations.
Keywords: dysfibrinogenemia; knob A mutations; thrombosis; Aα Arg19Gly; SNP